A conflict detection and resolution scheme using dynamic flight model - He, X.J.; Liao, M.Z.W.; Chen, W.F. (2009 International Conference on Machine Learning and Cybernetics, 2009)
In this paper, we propose a conflict detection and resolution scheme of multi aircrafts for an intersection region of two aircraft flows. The scheme is based on dynamic flight models, which allows the status of aircrafts is checked constantly. Therefore, we can detect conflicts in real-time and determine the conflict resolution scheme based on optimal control theory and speed change. In order to demonstrate the validity of our scheme, two examples are designed: one is two aircrafts and the other is three aircrafts. These two examples show that the scheme is safe.